THE IMPACT OF COVID-19 PANDEMIC ON OCCUPANCY RATES IN KLUANG MALL COMMERCIAL CENTRE - Azlina Md. Yassin; Mohd. Yamani Yahya; Haryati Shafii; Md. Asrul Nasid Masrom; Haidaliza Masram (International Journal of Property Sciences (E-ISSN: 2229-8568), 2022)
The Malaysian economy experienced negative growth in the retail industry during the COVID-19 pandemic. The widespread transmission of COVID-19 had impacted local companies and businesses in loss of businesses in the retail segment, the decrease in occupancy rates as reported by the Department of Statistics Malaysia (DoSM), and retail marketing strategy in the time of crisis. This paper aims to study the impact of the COVID-19 pandemic on occupancy rates and to identify the main factors influencing occupancy rate performance in Kluang Mall during the pandemic season. This study adopted a qualitative research approach throughout the research process. The results were based on the interview conducted at Kluang Mall Commercial Centre which is located in Kluang, Johor. Three (3) officers who are part of the management team were interviewed online as representatives of Kluang Mall Commercial Centre. The interview session discovered that the COVID-19 pandemic did not impact the occupancy rates of the Kluang Mall as the percentage remains the same as the previous period prior to the pandemic. The factors that contributed to the occupancy rate performance were the sales performance and the current marketing strategy applied by the management of the mall during the pandemic. Thus, it is hoped that these findings would assist retailers to improve their business performance, especially during the pandemic, and assist the Kluang Mall management team in managing retailers.